Clinical significance of diagnostic algorithm in detection of mild hemostasis disorders in women with menorrhagia - Djukic, Svetlana; Andjelkovic, Nebojsa; Vukomanovic, Vladimir; Simic-Vukomanovic, Ivana; Djukic, Aleksandar; Antovic, Jovan (Vojnosanitetski pregled, 2020)
Background/Aim. Coagulation disorders could be a cause of menorrhagia in women of reproductive age. The aim of the study was to estimate frequency of coagulation disorders and design an appropriate algorithm for detection of coagulation disorders. Methods. We investigated coagulation in 115 women (36.1 ? 9.6 years) with anamnestic data of menorrhagia, verified using semiquantitative method ? Pictorial Bleeding Assessment Chart (PBAC) with score ? 100. Results. Menorrhagia was objectively verified in sixty-four women (55.7%) and in comparison with those with normal menstruation they had higher PBAC score of menstrual cycle [median (Md) = 150.0 vs. Md = 50.0; p < 0.001] but not its duration (7.2 ? 2.1 days vs. 7.3 ? 1.9 days; p > 0.05). Coagulation defects was found in 12 (10.4%) women ? decreased F IX: Ac in 4 (3.5%), decreased F VII: Ac in 1 (0.9%), decreased F X: Ac in 1 (0.9%), decreased F XI: Ac in 1 woman (0.9%), while 5 (4.3%) women matched criteria for mild von Willebrand disease (VWD) type 1. Women with coagulation disorders had prolonged prothrombin time (PT) [Md = 13.1 s, range: 12.2?14.8 s vs. Md = 12.5 s, range 10.6?18.3 s; p = 0.032]. Anemia was diagnosed in 61 (53.0%) women. The strongest predictor of the hemostasis disorder was menorrhagia (Quotient of probability 0.018), then anemia presence (12.43), P? (2.35), menstrual cycle duration (1.16) and the PBAC score (0.98). Conclusion. The results of the study indicate the need to form a diagnostic algorithm for hemostasis disorders, primarily VWD. Sophisticated analysis of hemostasis is required, especially if predictive factors of statistical models are detected: objectively verified menorrhagia, anemia, prolonged menstrual cycle, PBAC score > 100 and extended PT. nema